Principles of Information Systems - Stair, Ralph M.; Reynolds, George Walter; Bryant, Joey; Frydenberg, Mark; Greenberg, Hollis; Schell, George P. (Cengage learning, 2021)
Develop an understanding of the core principles of information systems (IS) and how these principles make a difference in todays business environment with Stair/Reynolds' PRINCIPLES OF INFORMATION SYSTEMS, 14E. Completely reorganized for clarity and focus, this fresh new edition provides engaging new chapter opening cases and a new chapter on AI and automation. You explore the challenges and risks of cybercrime, hacking, internet of things, and artificial intelligence as you examine the latest IS research and learn from memorable examples. You can even maximize your employability as you learn how to use IS to increase profits and reduce costs in organizations. You study the latest in big data, business intelligence, cloud computing, e-commerce, enterprise systems, mobile computing, strategic planning, and systems development. Powerful tools, such as new ConceptClip videos and You Make the Decision interactive cases in this editions MindTap digital resources help you further your success.